Ventrikel Kanan Berbilik Ganda pada Pasien Dewasa: Temuan Insidental dengan Gambaran Khas Ekokardiografi Transtorakal - Desita Asri Yulistina; Putri Dwi Anggreheni; Putri Isa Maharani Yaasiin; Rafif Ryandra Izdhihar; Nanda Nurkusumasari (Jurnal Kardiologi Indonesia, 2026)
Background: A Double Chambered Right Ventricle (DCRV) is an uncommon congenital heart defect in which an abnormal muscular bundle divides the Right Ventricle (RV) into two chambers with different pressure levels. Diagnosing DCRV in adults is challenging because it is often asymptomatic and may be misdiagnosed. Case Illustration: We present a 37-year-old male with a history of an uncorrected Ventricular Septal Defect (VSD), who was incidentally found to have type 2 DCRV on echocardiography during evaluation for abdominal pain. No residual VSD was detected, possibly due to spontaneous closure. Electrocardiography (ECG) revealed first-degree Atrioventricular (AV) block. Chest radiography showed cardiomegaly with a Cardiothoracic Ratio (CTR) of 0.56. Transthoracic Echocardiography (TTE) demonstrated an anomalous muscular bundle that divided the RV into a high-pressure proximal chamber and a low-pressure distal chamber, accompanied by left atrial and ventricular enlargement. Conclusion: DCRV in adults is often misdiagnosed as pulmonary stenosis, especially in patients with mild or no symptoms. TTE and Doppler imaging are key diagnostic modalities for accurate diagnosis; however, advanced imaging techniques such as Transesophageal Echocardiography (TEE) may be required in complex cases. Management includes symptom control, such as beta-blockers, and further evaluation to determine the need for surgical intervention.